2000
DOI: 10.1053/rmed.2000.0825
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrogen peroxide generation and the content of lipid peroxidation products in lung cancer tissue and pulmonary parenchyma

Abstract: Lipid peroxidation, as a well-known index of reactive oxygen species activity, not only in lung biochemistry, is an oxidative process associated with membrane lipid destruction. Also, the oxidative modification of nucleic acids by reactive oxygen species is of remarkable biological importance as it may contribute to malignant conversion, but its exact role in lung cancer biology is still not clear. Our study aimed to investigate the level of lipid peroxidation ex vivo in tumour tissue and lung parenchyma obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 19 publications
3
63
0
Order By: Relevance
“…Enzyme has two forms, cytoplasmic (Cu,Zn-SOD) and mitochondrial (Mn-SOD) superoxide dismutase (23). Several investigators have reported that in lung cancerous tissue the activities of antioxidant enzymes were generally lower than in normal lung tissue (24). In our study, we observed that significant decrease in SOD activities in lung cancer patients leads to a net increase in the level of the superoxide free radical.…”
Section: Discussionsupporting
confidence: 57%
“…Enzyme has two forms, cytoplasmic (Cu,Zn-SOD) and mitochondrial (Mn-SOD) superoxide dismutase (23). Several investigators have reported that in lung cancerous tissue the activities of antioxidant enzymes were generally lower than in normal lung tissue (24). In our study, we observed that significant decrease in SOD activities in lung cancer patients leads to a net increase in the level of the superoxide free radical.…”
Section: Discussionsupporting
confidence: 57%
“…•-and H 2 O 2 found in these cells (49)(50)(51)(52)(53), supports the idea that cancer cells have this alteration in the metabolism of O 2 . This alteration may play a crucial role in carcinogenesis by allowing the activation of glycolysis in the presence of O 2 and, therefore, the uncontrolled cell proliferation that characterizes cancer ( Figure 1B).…”
Section: Key Role Of Altered Oxygen Metabolism In Cancersupporting
confidence: 79%
“…They showed, for instance, that a concentration of 50 μmol/L H 2 O 2 induced a higher percentage of cell death in Burkitt lymphoma cells than 250 μmol/L in normal lymphocytes and normal monocytes (108). In vitro and in vivo data indicate that tumor cells produce higher concentrations of H 2 O 2 than their normal counterparts (49)(50)(51)(52)(53). These data, and the fact that there is a threshold of H 2 O 2 above which cells cannot survive, may explain why specific concentrations of H 2 O 2 induce selective killing of cancer cells (36).…”
Section: Selective Killing Of Cancer Cells By H 2 O 2 and Prooxidantmentioning
confidence: 99%
“…57,58 It has also been reported that spontaneous generation of ROS in tumor tissue was positively correlated with clinical stage in small cell lung cancer and squamous cell carcinoma patients. 59 In prostate cancer patient tissue, manganese superoxide dismutase antioxidant enzyme levels have been reported to be lower while nuclear oxidative damage products are higher in metastatic tissue as compared with primary tissue, suggesting that increased ROS due to repression of antioxidants may contribute to DNA damage and prostate cancer. 60 ROS has also been suggested to mediate EMT.…”
Section: Canonical Pathways Of Snail In Prostate Cancermentioning
confidence: 99%